2017
DOI: 10.1186/s13048-017-0361-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic analysis for Chinese patients with stage I ovarian endometrioid carcinoma

Abstract: BackgroundThis study aimed to identify the clinical and pathological characteristics and the possible prognostic factors for Chinese patients with early-stage ovarian endometrioid carcinoma.MethodsThe present study reviewed the medical records of patients who received initial treatment and a postoperative pathological diagnosis of ovarian endometrioid carcinoma at our center. In all, 78 patients had stage I ovarian endometrioid carcinoma.ResultsIn this series, the 5-year overall survival rate and 5-year diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The major factors that affect the prognosis in univariate analysis were reported as the following: menopausal status, FIGO staging, histological grade, lymph node dissection, ascites cytology, and hormone receptor expression. The main factors that significantly affect prognosis in multivariate analysis are grade 3 and lymph node dissection ( 111 , 145 ). Among them, FIGO staging is the most significant factor.…”
Section: Prognosis and Independent Prognostic Factorsmentioning
confidence: 99%
“…The major factors that affect the prognosis in univariate analysis were reported as the following: menopausal status, FIGO staging, histological grade, lymph node dissection, ascites cytology, and hormone receptor expression. The main factors that significantly affect prognosis in multivariate analysis are grade 3 and lymph node dissection ( 111 , 145 ). Among them, FIGO staging is the most significant factor.…”
Section: Prognosis and Independent Prognostic Factorsmentioning
confidence: 99%
“…Patients with stage IA/IB ovarian EC have a 5‐year survival of more than 95%, and the current consensus is that these patients can be spared adjuvant systemic therapy unless an undifferentiated component is diagnosed. However, the management for some stage IC patients has been called into question because their survival also seems to approach the 95% threshold . Thus, it is of importance to develop simple and reliable risk stratification methods to identify high‐risk patients who will benefit from systematic therapy, while sparing low‐risk patients the toxic side effect of multi‐agent chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the management for some stage IC patients has been called into question because their survival also seems to approach the 95% threshold. [2][3][4][5] Thus, it is of importance to develop simple and reliable risk stratification methods to identify high-risk patients who will benefit from systematic therapy, while sparing lowrisk patients the toxic side effect of multi-agent chemotherapy. Multiple studies have aimed to identify prognostic biomarkers to help oncologists to stratify patient populations.…”
Section: Introductionmentioning
confidence: 99%
“…Among cases of stage I endometroid carcinoma, Chao at el. also found that grade 3 tumors were an independent poor prognostic factor in terms of PFS 22 . However, it remains controversial whether grade correlates with unfavorable survival outcomes in mucinous carcinomas 23 .…”
Section: Second Malignancies Among Women With Early-stage Eoc Who Fssmentioning
confidence: 79%
“…It is di cult to distinguish whether the second malignancy was a metastatic endometrioid endometrial cancer from the ovary or a synchronous cancer. Zhao et al reported thatpatients with stage I ovarian endometrioid carcinoma had a 19.3% rate of synchronous early stage and well-to-moderate differentiated endometrial carcinoma 22 . Notably, in our study, uterine cancer also developed in patients with ovarian cancerof the other histologies.…”
Section: Second Malignancies Among Women With Early-stage Eoc Who Fssmentioning
confidence: 99%